2019
DOI: 10.1155/2019/8591623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of on-Board Unit on Driving Behavior in Connected Vehicle Traffic Flow

Abstract: Connected vehicle technology has potentials to increase traffic safety, reduce traffic pollution, and ease traffic congestion. In the connected vehicle environment, the information interaction among people, cars, roads, and the environment is significantly enhanced, and driver behavior will change accordingly due to increased external stimulation. This paper designed a Vehicle-to-Vehicle (V2V) on-board unit (OBU) based on driving demand. In addition, a simulation platform for the interconnection and communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Indeed, in (Ali et al, 2020), the authors have found that this approach of driver notification trough the connected environment improve the behavior of the driver in terms of safety when communications are well-established. In (Chang et al, 2019), the effect of an onboard unit (OBU) as a V2V technology has been analyzed in different traffic scenarios. Based on the analysis presented in their work, the authors found that the use of onboard units has a positive impact on drivers' driving behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, in (Ali et al, 2020), the authors have found that this approach of driver notification trough the connected environment improve the behavior of the driver in terms of safety when communications are well-established. In (Chang et al, 2019), the effect of an onboard unit (OBU) as a V2V technology has been analyzed in different traffic scenarios. Based on the analysis presented in their work, the authors found that the use of onboard units has a positive impact on drivers' driving behaviors.…”
Section: Related Workmentioning
confidence: 99%
“…Intersection collisions account for over 40% of total traffic accidents, which not only seriously threaten people's lives, but also cause severe traffic congestion [2]. Research has shown that over 60% of these collisions can be avoided if drivers receive a warning just half a second in advance [3,4]. To improve traffic problems and build smart cities, the intelligent transportation system (ITS) has been widely studied [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of connected vehicles (CVs), research on tra c ow theory has gradually evolved from traditional tra c ow modeling to connected tra c ow [10][11][12][13][14][15][16]. A CV can share its status (e.g., position, speed, and acceleration) with other CVs within a certain range via vehicle-to-vehicle (V2V) or vehicle-to-infrastructure (V2I) communication.…”
Section: Introductionmentioning
confidence: 99%